Sukkerroe-Kulturens Betydning for det mindre Jordbrug. Diskussion, d. 11te Febr. 1874. - Tuxen, Redaktør (Tidsskrift for Landøkonomi, 2018)
Sukkerroe-Kulturens Betydning for det mindre Jordbrug. Diskussion, d. 11te Febr. 1874.